The Effects of Aquatic Watsu Therapy on Gross Motor Performance and Quality of Life for Children with Cerebral Palsy - (:unkn) unknown (MONTENEGRIN SPORTS ACAD, 2021)
The purpose of this study was to compare the effects of Immersion and Watsu (R) therapy protocols on children with cerebral palsy. Gross motor function (GMF), spasticity (MAS), and Quality of Life (QoL) parameters of twenty-three children (age: 7.5 +/- 2.8, BMI: 17 +/- 3.7) were measured. Subjects received Watsu (R) therapy and Immersion protocols in Watsu-Immersion (W-I, n=12) and Immersion-Watsu (I-W n=11) groups in different periods based on a crossover design. The subjects received sessions for 30 minutes twice a week during 10-week experimental periods. The results were investigated with independent sample t-test and Wilcoxon rank-sum tests, which showed that there was no evidence of carryover effects in GMFM 88 and QoL. In contrast, Watsu (R) improved GMFM 88 (p<0.05), Quality of Life (p<0.05), and MAS-Upper spasticity (p<0.05), scores significantly compared to immersion. The current results demonstrated the specific benefits of Watsu (R) therapy on children with CP, confirming the previous anecdotal reports. We recommend Watsu (R) as a safe and well-accepted complementary intervention for the management of CP.
Keywords: Watsu (R); cerebral palsy; immersion; motor function; quality of life; RELIABILITY